Analisis Kinerja Sistem Antrian di Loket Administrasi BPJS Kesehatan - Dewi Puspa; Rahma Yeni (Journal of Nursing Education and Practice, 2025)
Introduction: The performance of the queuing system is often associated with the quality of service received by users. Although online services are available, there is still a problem of queue buildup in providing insurance administration services for the JKN-KIS program at BPJS Kesehatan Cibinong Branch, Bogor Regency. Objectives: The purpose of this study was to analyze the performance of the queuing system at the administrative counter of the BPJS Kesehatan Cibinong Branch Office. Method: This research uses a qualitative approach with a case study, which focuses on the performance of the queuing system at the administrative counter of the BPJS Kesehatan Cibinong Office. Data obtained from observations, calculations, and processing using the Multi Channel Single Phase (M/M/3) queue model: (FIFO/∞/∞). Result: The study revealed that the highest queue buildup occurred between 09:01 and 10:00, with 157 participants, an average of 24.2 people in line, and 27.09 people waiting in the system. In contrast, the lowest queue was observed between 13:01 and 14:00, with 64 participants and almost no waiting time. The longest average waiting time in the queue was 0.93 minutes, and the shortest was 0.01 minutes, while the total time in the system ranged from 1.04 minutes at peak hours to 0.12 minutes at off-peak hours. Conclusion: This finding is expected to serve as a basis for improving the efficiency and quality of service in the queuing system at BPJS Kesehatan Cibinong Branch.